Induction of base substitution mutations by aflatoxin B1 is mucAB dependent in Escherichia coli. - Foster, P L (1988)
Recovery of aflatoxin B1-induced base substitution mutations in Escherichia coli was almost completely dependent on the presence of the SOS-mutagenesis-enhancing operon mucAB+; the normal E. coli analog, umuDC+, was not sufficient. Yet aflatoxin B1 induced the SOS response, including the umuDC operon, as well as did UV light. Neither preinduction of the SOS response nor the presence of additional copies of umuDC+ allowed the recovery of aflatoxin B1-induced base substitutions. Thus, the premutagenic DNA lesions induced by aflatoxin B1 reveal a functional difference between UmuDC and MucAB. We estimate that in the presence of MucAB the probability that aflatoxin B1-induced DNA lesions will be converted into mutations is increased at least 10-fold.